Healthy landscapes, healthy people: living landscapes as sites for the integration of heritage and modern health knowledges - Martin Mickelsson; Caleb Mandikonza; Rob O’Donoghue (Critical Public Health)
This paper explores social-ecological relational dynamics in health knowledge and practices in health education relating to the social practices of government and communities, and how the microbial world could be relationally normalized for better health and well-being of individuals and communities. A case study methodology is operationalized, focusing on cholera in Zimbabwe in response to how human health practices in the ever-changing environment in Southern Africa are largely determined by an expert-driven and top-down scientific knowledge landscape grounded in colonial approaches. Communities view themselves as unable to contribute to addressing health challenges exacerbated by ecological, social, and infrastructural conditions. The findings highlight a dissonant relationship in which modern health approaches often marginalize heritage knowledge and practices regarding the relationships between human and environmental health in managing socio-ecological relationships. This paper shows how knowledge landscapes have real-world, ontological impacts on educational efforts to address the health challenges posed by cholera bacteria. A critical perspective is provided regarding the integration of heritage approaches to modern challenges in health education, offering knowledge for living with and within the environment. This study contributes to normalizing socio-ecological relationships in water bodies and human bodies and building social resilience to emerging human and environmental health challenges.